Home range sizes for burchell's zebra equus burchelli antiquorum from the Kruger National Park - G.L. Smuts (Koedoe: African Protected Area Conservation and Science, 1975)
Annual home range sizes were determined for 49 marked zebra family groups in the Kruger National Park. Sizes varied from 49 to 566 sq. km, the mean for the Park being 164 square kilometre. Mean home range sizes for different zebra sub-populations and biotic areas were found to differ considerably. Present herbivore densities have not influenced intra- and inter-specific tolerance levels to the extent that home range sizes have increased. Local habitat conditions, and particularly seasonal vegetational changes, were found to have the most profound influence on the shape and mean size of home ranges. The large home range sizes obtained in the Kruger Park, when compared to an area such as the Ngorongoro Crater, can be ascribed to a lower carrying capacity with respect to zebra, large portions of the habitat being sub-optimal, either seasonally or annually.